THE ACQUISITION OF CONVERSATIONAL IMPLICATURES BY A FIVE YEAR OLD INDONESIAN CHILD - Rafika Purba (Jurnal Mantik Penusa, 2018)
The aim of this study was to describe types, processes and reasons of the conversational implicatures uttered by a five-year-old Indonesian child. The subject is the writer’s own son living in Lau Dendang, Kec Percut Sei Tuan, Kab Deli Serdang. It was a qualitative research design which was observed with a single case study. The instruments used were observation and interview. The researcher observed the subject for three months where conversation in different contexts in daily activities took place. An interview toward the subject’s care givers was conducted to get the subject’s reasons in uttering the conversational implicatures in his daily activities. The data collected were the utterances spoken by the subject in different contexts and interview. The data were analyzed by using the theory of language acquisition and conversational implicatures. The results of this study were: (1) The two types of conversational implicatures namely generalized conversational implicature involving clausal implicature and scalar implicature and particularized conversational implicature were uttered by the subject in his daily activities in different contexts. (2) The process of producing conversational implicatures occurred by flouting maxims. (3) The reasons of using conversational implicatures based on the maxim analysis were : to say opinion, to advise,  to refuse, to defend self, to make a joke, to guess, to do something soon, to inform, to say like, to ask something, to say dislike, to avoid discomfort,  to ask help, to avoid quarrel, to stay at something, to avoid the next question, to play imagination, to change like and to imitate. The reasons of using conversational implicatures based on the speakers’ background analysis was the interaction in community. Key Words : Language Acquisition, Conversational Implicatures, Flouting Maxims